Theta burst stimulation promotes nestin expression in experimental autoimmune encephalomyelitis - Ninković Milica B.; Milosavljević Petar; Maličević Bojana; Stojanović Ivana; Ilić Tihomir V.; Ilić Nela; Stevanović Ivana D. (Vojnosanitetski Pregled)
Background/Aim. Multiple sclerosis (MS) is an immune-mediated disease of the nervous system in which the myelin sheath is destroyed during the process of neurodegeneration. Experimental autoimmune encephalomyelitis (EAE) is an animal model of MS in which preservation of myelin and remyelination of axons can improve neuron survival. The aim of the study was to evaluate the activation capacity of neuronal tissue by autoimmune inflammation and treatment with intermittent (i) theta burst stimulation (TBS)- iTBS or continuous TBS (cTBS) based on the expression profiles of nestin in astrocytes, oligodendrocytes, and neurons. Methods. Two forms of TBS – iTBS and cTBS – were used to extend the period during which axons can be remyelinated. It was investigated how iTBS or cTBS protocols affect the expression profiles of nestin with glial fibrillary acidic protein, myelin basic protein (MBP), and neuronal nuclear protein in rat spinal cord. Changes at the molecular level were monitored using the immunofluorescence method. Results. The obtained results showed that both protocols (iTBS and cTBS) increased the expression of nestin and MBP and reduced astrogliosis in the spinal cord of EAE rats. Conclusion. The therapeutic potential of TBS in EAE contributes to the improvement of the intrinsic ability to recover from spinal cord injury.